Antioxidant changes of leek (Allium ampeloprasum var. porrum) during spontaneous fermentation of the white shaft and green leaves. (14th February 2013) - Bernaert, Nathalie; Wouters, Dorrit; De Vuyst, Luc; De Paepe, Domien; De Clercq, Hervé; Van Bockstaele, Erik; De Loose, Marc; Van Droogenbroeck, Bart
Abstract Background Leek is grown for its thickened cylindrical white shaft made up of long leaf bases. Despite the potentially valuable nutritional profile of the green leaves, a large portion remains unused owing its restricted culinary applications. This large quantity of this plant biomass could be valorized given an adequate stabilization method. In this study, we examined leek fermentation with regard to antioxidant changes. Results The oxygen radical absorbance capacity (ORAC) increased by 62% when the green leaves were fermented for 21 days, while 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging activity did not increase significantly. Fermentation resulted in an increase of endogenous polyphenolic compounds such as ferulic acid, astragalin, luteolin and naringenin. Moreover, fermentation stimulated the production of a series of polyphenolic compounds that were not present in the fresh leek. The flavour precursors in leek, i.e. methiin and isoalliin, were reduced by 91–93% and 100%, respectively, when spontaneous fermentation was allowed to occur on the white shaft and green leaves. Conclusion Our results demonstrated that application of fermentation resulted in a higher ORAC value and polyphenol content of the leek plant, especially in the green leaves. These results indicate the nutritional relevance of fermentation, which hold promise as a stabilization technique. © 2013 Society of Chemical Industry